Production performance of goat in field condition: A survey in semi-arid zone of Uttar Pradesh, India - KUMAR, VIJAY; SINGH, B P; DUTT, TRIVENI (The Indian Journal of Animal Sciences, 2016)
Goats make important contributions to the stability of smallholder farming system by providing financial resources for purchase of farm inputs and household needs, nutritional security, skin and fibers, employment and organic manure. In the recent study, a total of 240 goat farmers of two districts (Firozabad and Mainpuri) of the semi-arid zone of Uttar Pradesh, India were interviewed. Weight of 227 goats (£1 year) were taken by spring balance and information regarding production performance of different traits were collected by interview of goat farmers. Based on the results, goat farmers were classified into three categories viz. landless (25.8%), marginal (54.2%) and small and semi-medium (20%), respectively. Milk yield of Sirohi, Barbari and non-descript breeds were 0.9, 0.6 and 0.8 liter/day, respectively. Jakhrana breed of goat had highest weight irrespective of age and sex, whereas Barbari has lowest among all breeds found in the study area. Dilution of pure breed line and low adoption of recommended management in the study area were important factors for low productivity. Total mortality rate in goat was 21.16% which was highest among 1–3 months old followed by 3–6 months and above 6 months age group, respectively. Age of first kidding, kidding interval and kidding % of non-descript breed in the field were 17.6 months, 11.4 months and 1.29, respectively. There was positive correlation between number of buck kept by farmers and their flock size. Buck of Sirohi breed were most preferred by farmers (72.4%) in study area.